2016
DOI: 10.1242/jcs.181263
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear size is sensitive to NTF2 protein levels in a manner dependent on Ran binding

Abstract: Altered nuclear size is associated with many cancers, and determining whether cancer-associated changes in nuclear size contribute to carcinogenesis necessitates an understanding of mechanisms of nuclear size regulation. Although nuclear import rates generally positively correlate with nuclear size, NTF2 levels negatively affect nuclear size, despite the role of NTF2 (also known as NUTF2) in nuclear recycling of the import factor Ran. We show that binding of Ran to NTF2 is required for NTF2 to inhibit nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
59
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 66 publications
11
59
0
Order By: Relevance
“…In case of importins and exportins, previous work has shown they can be functionally tagged (Miyamoto et al , 2002; Ciciarello et al , 2004; Kimura et al , 2013b; Vuković et al , 2016). This is very well reflected in our data, for example, biotinylated cargos accumulate in the expected cellular compartment over time and known interactors are among the most prominently identified proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In case of importins and exportins, previous work has shown they can be functionally tagged (Miyamoto et al , 2002; Ciciarello et al , 2004; Kimura et al , 2013b; Vuković et al , 2016). This is very well reflected in our data, for example, biotinylated cargos accumulate in the expected cellular compartment over time and known interactors are among the most prominently identified proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that RGP primary melanoma cells exhibit larger nuclei compared to normal melanocytes. We also found that the levels of Nuclear Transport Factor 2 (NTF2) inversely correlate with nuclear size, with decreasing NTF2 levels in melanoma progression correlating with increased nuclear size (Vukovic et al, 2016).…”
Section: Introductionmentioning
confidence: 72%
“…[42][43][44] The size of the nucleus is similarly much larger in X. laevis than X. tropicalis, and is sequentially reduced further during embryonic cleavage stages, enabling the use of these species for investigations of nuclear scaling. The size of the nucleus has been found to also be regulated by Importin α, as well as NTF2, 45,46 and Lamin components. 47,48 Nuclear envelope composition is particularly interesting in Xenopus, as it contributes to regulatory events such as the mid-blastula transition 49 as well as nuclear morphological features such as nuclear branching.…”
Section: Unique Opportunities For Comparative Cell Biologymentioning
confidence: 99%